The Effects of Project-Based Learning on the Learning Skills of 21st Century Nursing Students at Boromarajonani College of Nursing, Buddhachinaraj - Yodprong, Subhawan; Kaewdoo, Kanitta; Ar-yuwat, Sireewat; Poonsub, Apiched (Thai Red Cross Nursing Journal, 2023)
This quasi-experimental, one-group pretest-posttest study aimed to compare the mean scores of nursing students on their 21st century learning skills after completing a course utilizing project-based learning. Purposive sampling was used to recruit 142 participants, who were fourth-year nursing students at Boromarajonani College of Nursing, Buddhachinaraj, enrolled in the "Community Nursing Practicum II" course. Data were collected using the 21st century learning skills questionnaire, which was validated for content by five experts. The index of item objective congruence for this research instrument was .73, and the Cronbach's alpha coefficient was .97. Data were then analyzed using descriptive statistics and the Wilcoxon signed-rank test. After completing the course, the overall and 13 subscale mean scores on the students’ 21st century learning skills were significantly higher than before the intervention (p-value < .01). These results suggest that project-based learning is an effective approach in this context; as such, project-based learning could be utilized by nursing instructors and academic administrators to enhance nursing students' 21st century skills.